PENGARUH, FASILITAS, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ZEBRA ASABA INDUSTRI, JAKARTA BARAT - Mudofar, Mudofar (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
The purpose of this study is to determine the effect of facilities, motivation, and workdiscipline on the work performance of PT Zebra Asaba Industrui employees. The research methodused is descriptive method with regression and correlation approaches which is a method that aims todescribe the influence and relationship of something that is going on at the time the research isconducted. The results of this study indicate partially or simultaneously facility variables,motivation, and work discipline have a significant effect on employee performance. The magnitude ofthe correlation value (R) is 0.924 which means that there is a strong correlation / relationshipbetween facilities, motivation, and work discipline with employee performance. The amount ofadjusted coefficient of determination (R2) is 0.793 or 79.3%, which means that independentvariables can explain changes in employee performance variables by 79.3% while the remaining20.7% is explained by other factors beyond this research.